Development of simplified treatment methods for removal of Ra-226 and Ra-228 from sludge waste produced in natural gas processing plants - Ayman M. Sharaf; M.A. El-Nahal; Islam M. Nabil; I.H. Saleh; Mohamed Elsafi (Nuclear Engineering and Technology)
The present study aims to establish a new treatment method for removing or reducing the concentration of 226Ra and 228Ra in sludge waste produced due to natural gas production at natural gas processing Plants. The main radionuclides present in sludge waste of natural gas processing are Radium and its daughters due to their low solubility in the water they can form compounds with sulfate ions, carbonate ions, silicate ions, then precipitation scale or sludge. The suggested method is designed to be simple, applicable, economically beneficial, and environmentally safe, by using internal available resources like emitted hydrogen sulfide and sodium hydroxide, also reduction of chemicals that used in radioactivity treatment to be sulfuric acid or sodium hydroxide instead of multiple different chemicals that used in other treatment procedures. The effects of the used chemical reagents sulfuric acid and sodium hydroxide in various concentrations at different reaction temperatures on the sludge waste to extract the radium isotopes have been studied, evaluated, and compared. The study proved that removing radium isotopes is increased by elevating the reagents concentration and sludge temperature. The removal effects of the used reagents are approximately similar.